HACCP IN IRANIAN CAVIAR - Moradi., Yazdan (Emirates Journal of Food and Agriculture, 2017)
There are twenty four existing sturgeon species world wide. Five of them live in the Caspian Sea and supply caviar: Huso huso, Acipenser guelden staedtii, Acipenser persicus, Acipenser nudiventris, and Acipenser stellatus. Caviar production has many processing steps. In the first the landed fish are numbered and washed several times, then gutted to remove roes and resultant roes are washed and strained through screens in order to remove any connective tissues. The next step of processing caviar is salting. The type of salt used depends on the customer's preference and the customs regulations of the purchasing country. Then caviar is filled in containers andthe lid is placed on it with utmost caution to compact the mass and remove the containair inside the container. At the end, a simple rubber band is pulled over the lid at the point contacting with the container. It should be noted that the liquid that seeps out of the container during storage is an indication of caviar's freshness. Iranian caviar has used HACCP for many years. In this article caviar HACCP will be described.